Association of grass pollen concentration and physical symptoms as well as impairments in day-to-day life in pollen allergy patients - V. Landesberger; J. Huß; K. Grenzebach; D. Nowak; M. Gröger; E. Oppel; B. Schaub; L. E. French; S. Kutzora; C. Quartucci; C. Herr; S. Heinze (Scientific Reports)
Abstract Allergic diseases are a major global public health issue, profoundly impacting the daily lives of millions of people worldwide. The aim of this study is to investigate the association between daily grass pollen concentration and daily physical symptoms as well as impairments in day-to-day life in pollen allergy patients in Bavaria, Germany over a period of three-months. Pollen data of the pollen season 2022 were obtained from the electronic pollen information network of Bavaria. We used an app-based questionnaire and developed an index to measure physical symptoms—regarding eyes and nose as well as impairments in day-to-day life including performance, sleep quality and daily activities. For our analyses we used data from 53 patients. The associations were analysed using linear mixed models (LMM). We found a statistically significant association between the level of grass pollen concentration and both the index physical symptoms (β = 0.002; p < 0.001) and the index impairments in day-to-day life (β = 0.00064; p < 0.048). It is important that patients are well informed about the pollen count as well as their physical symptoms and daily life impairments so that they can manage their allergies effectively and appropriately.